2016
DOI: 10.1115/1.4032891
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Venting Enhances the Replication of Nano/Microfeatures in Micro-Injection Molding Process

Abstract: Vacuum venting is a method proposed to improve feature replication in microparts that are fabricated using micro-injection molding (MIM). A qualitative and quantitative study has been carried out to investigate the effect of vacuum venting on the nano/microfeature replication in MIM. Anodized aluminum oxide (AAO) containing nanofeatures and a bulk metallic glass (BMG) tool mold containing microfeatures were used as mold inserts. The effect of vacuum pressure at constant vacuum time, and of vacuum time at const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Baruffi et al 16 identified that mold temperature and packing pressure significantly influence the outer ring diameter of microlenses, whereas the inner ring diameter is mainly affected by mold temperature and melt temperature. Gilchrist et al 17 concluded that the replication quality of high aspect ratio microstructures could be effectively improved by using vacuum aeration. Orth et al 18 found that the use of coated steel molds resulted in higher molding efficiency and 20% ~ 30% improvement in replication quality.…”
Section: Introductionmentioning
confidence: 99%
“…Baruffi et al 16 identified that mold temperature and packing pressure significantly influence the outer ring diameter of microlenses, whereas the inner ring diameter is mainly affected by mold temperature and melt temperature. Gilchrist et al 17 concluded that the replication quality of high aspect ratio microstructures could be effectively improved by using vacuum aeration. Orth et al 18 found that the use of coated steel molds resulted in higher molding efficiency and 20% ~ 30% improvement in replication quality.…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum venting is another type of technology that can be applied to µIM to improve part outcome and thus reduce energy costs. Ying Choi et al [8] have shown that by vacuum venting during the injection phase of the µIM process can create more defined features over larger areas and increased depths. Depth replication was improved by 1.33-7.52% and 0.88-5.94% by varying the vacuum pressure and time respectively.…”
Section: Introduction*mentioning
confidence: 99%